Os gêneros do discurso e a prática da produção textual: dialogando sobre os conhecimentos necessários aos educadores dos anos iniciais do ensino fundamental - Garcia, Stella de Lourdes (Universidade Federal de São Carlos, 2010)
The aim of this research was to verify and analyze which skills are necessary to the educators of 9-year-old pupils at the discourse genres as a teaching subject so that they can guarantee the pupils learning regarding the textual production which covers beyond the genre marks, i.e. the elements which ensure the discourse dynamics. Such skills were approached during an Extension Course in a dialogic collaborative process between researchers and educators, which was grounded in the development of a didactic sequence for the teaching of the writing discourse genre. It is an investigation of qualitative nature based on the dialogic collaborative methodology. The data collection was carried out during a continuing education course attended by educators and pupils from a municipal public school in São Carlos-SP which integrates the Project Learning Communities: betting on the learning quality, differences equality and democratization of the school management . We adopted a language conception which is constitutive of the individuals and used the studies by Freire, Bakhtin and researchers such as Schneuwly and Dolz as guidance. The data analysis, which was orientated by the assessment of themes present in the meetings with the educators as well as in the meetings with a third-year group of pupils, led us to conclude that the knowledge basis about teaching, more specifically the one regarding the knowledge of specific contents which refer to the discourse genres of the educators was not enough to guarantee that the discourse genres were conceived as a teaching subject. Although they were present in the classroom in reading activities, such a fact did not guarantee that the pupils appropriated them and started to produce them textually. As for the knowledge built during the education course, we believe that the reflections provided by the dialogic collaborative dynamics might have contributed to a change in the practice of the educators in question. We highlight the importance of the definition of the genre to be apprehended by the pupils, as well as the need to contextualize the writing process in an interlocutive situation, i.e. the pupils need to know what, why, how and to whom they write. Therefore, we can claim that using the didactic sequence to a writing genre teaching worked as instrumental to both the educators and the pupils. As for the educators, it provided methodological guidance to the systematized teaching of a writing discourse genre, thus contributing to the construction of a teaching knowledge basis; as for the pupils, it provided them with writing assurance, since they could learn and experience the knowledge and procedures which the textual production practice entails, taking into account the characteristics of the genre and the interlocutive situation.
Keywords: Educação elementar; Produção de textos; Gêneros discursivos; Professores - formação; Ensino fundamental; Textual production; Discourse genres; Elementary school; CIENCIAS HUMANAS::EDUCACAO